Dose-response study of inhaled salbutamol powder in chronic airflow obstruction. - Corris, P A (1983)
Dose-response relationships for salbutamol were studied in eight patients suffering from chronic airflow obstruction with no asthmatic features. Each inhaled, double blind, in randomised order 0, 200, 400, 800, and 1600 micrograms salbutamol on five successive mornings. Before and at intervals up to six hours after the inhalation FEV1, vital capacity, maximum inspiratory and expiratory flow-volume curves, and 12-minute walking distances were measured. Analysis of variance of the results indicated significant dose-response relationships and showed the larger doses to have a longer duration of action. Simple spirometric tests were as useful in providing objective evidence of benefit as maximum inspiratory flows or the 12-minute walking distance.